Junta Myanmar Akhiri Status Darurat: Manuver Politik Menuju Pemilu yang Dipertanyakan - Salsabilla, Tiara Zahira; Nurlia, Elly; Anastasya, Rahma Erliana; Lestari, Ananda Chanaya Meutya (Media Hukum Indonesia (MHI), 2025)
On July 31, 2025, Myanmar’s military junta, the State Administration Council (SAC), officially ended the state of emergency imposed since the February 1, 2021 coup, which ousted Aung San Suu Kyi’s National League for Democracy (NLD) government. This move, accompanied by plans for a caretaker administration and elections scheduled for December 28, 2025, and January 2026, is framed as a transition to democracy. However, this study, grounded in Hans Morgenthau’s Political Realism, argues it is a strategic maneuver to consolidate military power amid domestic resistance, ethnic conflicts, and international pressure. The coup, justified by alleged electoral fraud despite lacking evidence, triggered widespread civil unrest, armed conflict, and a humanitarian crisis, displacing millions. Using a qualitative descriptive method with a literature review, this research analyzes lhistorical context, junta strategies, potential electoral injustices, international responses, and regional stability impacts. Key theory  realist indicators: Balance of Power, Self-Interest and Survival, and International Anarchy reveal how the junta leverages alliances (e.g., with China) to counter Western sanctions, prioritizes survival over human rights, and exploits a fragmented global response. Findings suggest the elections may deepen ethnic divisions and instability, challenging ASEAN’s non-interference stance and highlighting the fragility of democratic transitions in Southeast Asia. The study calls for enhanced international pressure and inclusive dialogue to avert prolonged conflict.